Phytochemical Characterization of Mentha spicata L. Under Differential Dried-Conditions and Associated Nephrotoxicity Screening of Main Compound With Organ-on-a-Chip - Li, Xian; Tian, Tian (Frontiers in Pharmacology, 2018)
Spearmint (Mentha spicata L.) is normally used as a vegetable flavouring herb. It also has several pharmacological activities against fever, cough, infection and inflammation. The current study presents an untargeted comparative metabolomics approach utilizing HPLC-QTOF-MS high-throughput analytical technology to provide insights into the effect of the drying process on the examined spearmint species. To the best of our knowledge, this is the first report of compositional differences among fresh and dried spearmint leaves determined via a metabolomic approach to reveal that dried leaves are a better source of bioactive metabolites. The nephrotoxicity of kaempferol, a bioactive metabolite from spearmint, was further assessed with a kidney-on-a-chip. On the designed chip, a GelMA-based 3D culture platform mimics the microenvironment and basic functions of the kidney. In addition, the chip’s transparency allows for direct observation under an optical microscope. Treatment of human embryonic kidney cells with 30 μM of kaempferol for 12 h induced no obvious cell injury or apoptosis in the cells, on the basis of morphology, thus providing a proof-of-concept demonstration of kaempferol’s non-toxicity.